Role of infrapopliteal - Wael M. Wagdy (The Egyptian Journal of Radiology and Nuclear Medicine, 2016)
Objective: To compare the outcomes of infrapopliteal angioplasty between diabetic patients and non-diabetic patients with critical limb ischemia. Patients and methods: From March 2014 to December 2014, infrapopliteal angioplasty was performed on 60 limbs (43 men and 17 women with mean age 70.13 years) with the CLI (Fontaine’s grade III or IV). The number of diabetic patients was 40 (66.66%). Follow-up included clinical examination for rest pain improvement and ischemic ulcer healing, and duplex-documented target vessel patency or re-stenosis at discharge and at 3 months. Results: The technical success rate was 100% in diabetic and non-diabetic groups. The ulcer healing rate was 33/37 (89.18%) in diabetic patients vs. 14/15 (93.3%) in non-diabetic patients. And the re-stenosis and re-occlusion rates of treated vessels after 3 months were 10.0% in diabetic vs. 5.0% in non-diabetic groups. Conclusion: There were no significant differences between the 2 groups in the technical success rate, but the 3 months clinical success rate and the primary patency rate were better in non-diabetic than in diabetic patients with no significant differences.